Kemal Kılıçdaroğlu and the New Republican People’s Party in Turkey - Yavuz, M. Hakan. author. aut Link
X, 164 p. 1 illus.
Keywords: "Yavuz and Ozturk have masterfully crafted an outstanding examination of Kemal Kılıçdaroğlu's life, moral values, and political philosophy. Representing the first comprehensive study of the influential figure Kemal Kılıçdaroğlu, who played a pivotal role in shaping the political landscape of modern Turkey in its second century, this book is an essential resource for anyone seeking a profound understanding of the nation.” — Hüsamettin Cindoruk, Former Speaker of the Turkish Parliament “A timely, important, and path-breaking work by two eminent scholars on the man poised to become Turkey’s next president. This volume traces the rise, evolution, and world-view of Kemal Kılıçdarоğlu, whose victory would usher in a new era in Turkish politics.” — Paul Kupicek, Editor, Turkish Studies “With meticulous research and insightful analysis, Yavuz and Ozturk shed light on Kılıçdaroğlu's journey, offering invaluable insights into his beliefs, motivations, and impact on Turkey's trajectory. Their work stands as a testament to the significant contributions made by this transformative figure.” — Michael M. Gunter, Professor of Political Science, Tennessee Technological University This book discusses the life and professional struggle of Kemal Kılıçdaroğlu and the transformation of the CHP under his leadership. It deals with the transformational periods and phases of the CHP, up to the period when Kemal Kılıçdaroğlu became prominent in the party. Furthermore, this book aims to answer the following questions: How and for what reasons did Kılıçdaroğlu decide to ally with the center-right wing in the CHP? What was the collective impact of the center-right wing in positive and negative terms regarding the CHP’s general identity, especially in a historical context? After the 2015 elections, what constituted the shifts and revisions in Kılıçdaroğlu’s ideology and how did they alter the political power of the CHPas a major opposition party? What evidence exists to shed light on his capabilities for building coalitions as a viable option for the possibility of forming a national government in elections? M. Hakan Yavuz is Professor of Political Science at the University of Utah, US. Ahmet Erdi Öztürk is Associate Professor of Politics and International Relations at London Metropolitan University, UK.